Progress in Computational Physics (PiCP) Volume 1 : Wave Propagation in Periodic Media. - Ehrhardt, Matthias (Progress in Computational Physics (PiCP), 1., 2010)
Progress in Computational Physics is a new e-book series devoted to recent research trends in computational physics. It contains chapters contributed by outstanding experts of modeling of physical problems. The series focuses on interdisciplinary computational perspectives of current physical challenges, new numerical techniques for the solution of mathematical wave equations and describes certain real-world applications. With the help of powerful computers and sophisticated methods of numerical mathematics it is possible to simulate many ultramodern devices, e.g. photonic crystals structures.